Trauma Induced Calcium Pyrophosphate Deposition Disease of the Lumbar Spine - Indrit Greca; Jihad Ben Gabr; Andras Perl; Stephanie Bryant; Dan Zaccarini (Case Reports in Rheumatology)
Inflammatory arthritis, such as pseudogout or otherwise referred to as calcium pyrophosphate (CPP) crystal arthritis or calcium pyrophosphate deposition (CPPD) disease, is characterized by the deposition of crystal formation and deposition in large joints. CPPD is known to affect the elderly population and commonly manifests as inflammation of knees, hips, and shoulders. CPPD disease involving the spine has been infrequently encountered in practice and rarely described in the literature. Here, we describe a case of an 80-year-old female with no known history of inflammatory arthritis who presented with left lower extremity weakness and fall, initially thought to have discitis, later confirming CPPD of the spine through biopsy and ultimately resolution of symptoms with anti-inflammatory agents. Although consisting of different clinical presentations, two other case reports have described CPPD of the spine with similar radiographic findings, to this author’s knowledge. With the radiologic similarities, this unique case serves to raise awareness in the medical community and possibly place pseudogout of the spine on the differential list when such cases are encountered. As a result, patients can be initiated on benign anti-inflammatory agents, avoiding invasive testing and unnecessary antibiotic exposure.